JURIDICAL ANALYSIS OF THE PROVISIONS ON REST TIME FOR DOMESTIC WORKERS (PRT) IN INDONESIA - Ida Bagus Bayu Brahmantya (International Conference on Multidisciplinary Research Perspective, 2025)
Article 7 letter e of the Regulation of the Minister of Manpower Number 2 of 2015 concerning the Protection of Domestic Workers: “Domestic Workers have the right: e. to obtain sufficient rest time”, is still controversial regarding rest time which causes normative ambiguity. A juridical analysis is needed to understand the provisions on rest time for Domestic Workers in Indonesia. Therefore, this research is titled “Juridical Analysis of the Provisions on Rest Time for Domestic Workers (PRT) in Indonesia”, with the problem formulation being: what is the regulation regarding Domestic Workers based on the applicable statutory provisions in Indonesia and what is the legal certainty regarding the provisions on rest time for Domestic Workers in Indonesia.The type of research used is normative legal research, and the approaches used are the statutory approach and the conceptual approach, as well as using descriptive analysis.The conclusion is that the regulation related to Domestic Workers in Indonesia where Law Number 13 of 2003 concerning Manpower is more focused on formal employment, and the issuance of the Regulation of the Minister of Manpower Number 2 of 2015 concerning the Protection of Domestic Workers is important to protect Domestic Workers; legal certainty related to the provisions on rest time for Domestic Workers, especially the phrase "rest time" which is not specifically explained thus causing ambiguity in the application of rest rights. Suggestions to lawmakers regarding the regulation of Domestic Workers in Indonesia to ensure effective implementation and law enforcement, and to avoid normative ambiguity related to “sufficient rest time” by including a clear and specific definition regarding rest time, including duration, implementation time, and other related rights.